Interrogating human origins
1 online resource (xii, 352 pages)
Keywords: "Interrogating Human Origins encourages new critical engagements with the study of human origins, broadening the range of approaches to bring in postcolonial theories, and beginning to explore the decolonisation of this complex topic. The collection of chapters presented in this volume creates spaces for expansion of critical and unexpected conversations about human origins research. Authors from a variety of disciplines and research backgrounds, many of whom have strayed beyond their usual disciplinary boundaries to offer unique perspectives, all circle around the big questions of what it means to be and become human. Embracing and encouraging diversity is a recognition of the deep complexities of human existence in the past and the present, and it is vital to critical scholarship on this topic. This book constitutes a starting point for increased interrogation of the important and wide-ranging field of research into human origins. It will be of interest to scholars across multiple disciplines, and particularly to those seeking to understand our ancient past through a more diverse lens"--